Application of the Geo-informatics to Survey GUTTIFERAE Family Plants in Khok Phak Kut and Pong Daeng National Forest, Maha Sarakham Province - Prasertsri, Narueset; Sangpradid, Satith; Buasri, Nutchanat; Utta, Teeraya; Angkahad, Thinnakon; Butaka, Punya (Journal of Applied Informatics and Technology, 2021)
The plants of GUTTIFERAE family, from the local wisdom can be useful for eaten as a food and as a medicinal. The exploration the plants of GUTTIFERAE family in Khok Phak Kut and Pong Daeng, National Forest, Maha Sarakham Province. The aimes of this research are follows by 1) to exploratory the diversity of GUTTIFERAE 2) create a database and mapping distribution the plants of GUTTIFERAE, and 3) for plant genetic conservation planning. The 17 temporary plots size are 40 x 40 meters were laid out in the area. The results revealed that the plants 1,937 tree 38 species, 24 families, and found the plans of GUTTIFERAE 199 trees in 15 plots. The variety of GUTTIFERAE can be divided into 4 types: are followed by Cratoxylum formosum subsp. pruniflorum (Kurz) Gogel., Garcinia cowa Roxb. ex Choisy., Cratoxylum cochinchinense (Lour.) Blume, and the Gratoxylum formosum (Jack) Dyer. The total of tree is 96 44 39 and 20 respectively. The most Importance Value Index (IVI) are follow by 11.47 4.11 3.26 and 2.66 respectively, which the value in the moderately and quite a few level, when compared with other plants in the study area and in the survey plots. Therefor the Garcinia cowa Roxb. ex Choisy and the Gratoxylum formosum (Jack) Dyer, both of this plants are popular plant with people living around the forest to eat as fresh vegetables and as a flavorings of food, finally the plants should be more conservation to remain in the area.